ACUPUNCTURE AND AURICULOTHERAPY AS NON-PHARMACOLOGICAL PAIN RELIEF METHODS IN THE CHILDBIRTH PROCESS - Fabiane Cherobin; Arnildes Rodrigues Oliveira; Ana Maria Brisola (Universidade Federal do Paraná, 2016)
The childbirth process correlates the physiological changes with feelings and socio-cultural values. Pain is one of the important signals in this process. However, if uncontrolled, can cause many unwanted side effects. To minimize them, non-pharmacological methods can act to relieve pain. The aim of this study was to analyze the results of acupuncture and auriculotherapy as pain control, through a convergent care study, performed between June and September 2015. A total of 19 pregnant women in labor admitted to the obstetrics center of a public hospital of Santa Catarina agreed to participate in the study. Results showed 15 (79%) women feltpain relief in the first 30 minutes of the treatment. These results bring exciting prospects for labor care because the methods are inexpensive and safe, increasing the number of non-pharmacological alternatives for women in labor.